Tanda-Tanda Waqf dalam Tradisi Mushaf Al-Qur’an Cetakan Asia Selatan - Nurhikmatul Maulia; Ahmad Fathoni; Ziyad Ulhaq; Safri Ilman; Lukman Nur Hakim (Lajnah Pentashihan Mushaf Al-Qur'an, 2026)
This study aims to examine the use of waqf signs in the Karachi Mushaf and the Bombay Mushaf, along with their respective explanations. The classification is based on two categories of waqf, namely waqf qiyasiy scholarly ijtihad and waqf simaʿiy transmission through talaqqiy with a teacher. This classification can be identified by analysing the waqf signs placed inside the text frame of the mushaf, which represent waqf qiyasiy, and those placed outside the Qur’anic text frame, which represent waqf simaʿiy. This study employs library research and adopts a qualitative method using historical research, philological analysis, and the discipline of al-Waqf wa al-Ibtidaʾ. The primary data consist of the Karachi Mushaf published by Taj Company, Karachi, Pakistan, in 2012 CE, and the Bombay Mushaf published by PT Toha Putera, Semarang, in 1985 CE. The findings indicate that the Bombay Mushaf and the Karachi Mushaf are two distinct mushafs. The use of waqf signs in both mushafs reveals similarities and differences in several aspects. First, with regard to the types of waqf signs employed, both the Karachi Mushaf and the Bombay Mushaf contain 13 waqf qiyasiy signs and four waqf simaʿiy signs, although with several variations. Second, in terms of the number and placement of waqf signs, the Karachi Mushaf contains 657 waqf qiyasiy signs and 36 waqf simaʿiy signs, whereas the Bombay Mushaf contains 640 waqf qiyasiy signs and 35 waqf simaʿiy signs. Third, differences are also found in the method of writing or notating the waqf signs.